IMPLEMENTASI PENDIDIKAN MULTIKULTURAL PADA MATA PELAJARAN PPKn UNTUK MENUMBUHKAN SIKAP TOLERANSI PESERTA DIDIK - Randi Saputra; Sulistyarini Sulistyarini; Shilmy Purnama (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractMulticultural education is education that instills diversity principles in pupils so thatthey can live in harmony with one another. The purpose of this study is to discover theplanning, implementation, and implementation steps of multicultural education inCivics subjects at SMK Negeri 1 Teluk Keramat in order to foster a tolerant attitudeamong students. The research method used is descriptive with a qualitative researchapproach. Principals, PPKn subject teachers, and students were used as data sourcesin this study. Interviews and previous documentation are the only methods for gatheringdata. Researchers employed data collecting, data reduction, data presentation, andverification/drawing conclusions as stages of data analysis. The findings reveal thatmulticultural education in Civics courses at SMK Negeri 1 Teluk Keramat has beenproperly implemented, beginning with planning, implementation, and implementation,in order to build student tolerance. Multicultural education is incorporated into theplanning process.Keywords: Implementation, Multicultural Education, Tolerance